At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's write these given equations in their corresponding perpendicular forms. Perpendicular form typically means expressing the lines in the form [tex]\(Ax + By + C = 0\)[/tex] with appropriate coefficients.
1. Equation f): [tex]\(x + y - 2 = 0\)[/tex]
This equation is already in the perpendicular form. We don't need to make any adjustments:
[tex]\[ x + y - 2 = 0 \][/tex]
2. Equation iii): [tex]\(\sqrt{3} x - y - 2 = 0\)[/tex]
This equation is also already in the perpendicular form:
[tex]\[ \sqrt{3} x - y - 2 = 0 \][/tex]
3. Equation ii): [tex]\(x + \sqrt{3} y + 4 = 0\)[/tex]
This equation is in perpendicular form as well:
[tex]\[ x + \sqrt{3} y + 4 = 0 \][/tex]
4. Equation v): [tex]\(\sqrt{3} x + y - 2\sqrt{2} = 0\)[/tex]
This equation is correctly written in its perpendicular form:
[tex]\[ \sqrt{3} x + y - 2\sqrt{2} = 0 \][/tex]
5. Equation iv): [tex]\(-x + \sqrt{3} y + 4 = 0\)[/tex]
This equation is already in the desired form:
[tex]\[ -x + \sqrt{3} y + 4 = 0 \][/tex]
Thus, all the given equations were already expressed in their perpendicular forms.
1. Equation f): [tex]\(x + y - 2 = 0\)[/tex]
This equation is already in the perpendicular form. We don't need to make any adjustments:
[tex]\[ x + y - 2 = 0 \][/tex]
2. Equation iii): [tex]\(\sqrt{3} x - y - 2 = 0\)[/tex]
This equation is also already in the perpendicular form:
[tex]\[ \sqrt{3} x - y - 2 = 0 \][/tex]
3. Equation ii): [tex]\(x + \sqrt{3} y + 4 = 0\)[/tex]
This equation is in perpendicular form as well:
[tex]\[ x + \sqrt{3} y + 4 = 0 \][/tex]
4. Equation v): [tex]\(\sqrt{3} x + y - 2\sqrt{2} = 0\)[/tex]
This equation is correctly written in its perpendicular form:
[tex]\[ \sqrt{3} x + y - 2\sqrt{2} = 0 \][/tex]
5. Equation iv): [tex]\(-x + \sqrt{3} y + 4 = 0\)[/tex]
This equation is already in the desired form:
[tex]\[ -x + \sqrt{3} y + 4 = 0 \][/tex]
Thus, all the given equations were already expressed in their perpendicular forms.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.